THE STUDY OF THE INFLUENCE OF MODEL MEAT SYSTEMS ON THE ALLERGIC IMMUNE RESPONSE IN VIVO - A. S. Dydykin; M. Yu. Minaev; G. S. Tolmacheva; A. A. Musatova (Теория и практика переработки мяса)
This article presents the results of studying the eﬀect of homogeneous model meat systems produced using enzyme preparation containing fungal protease and microbiological starter culture of Lactobacillus plantarum on the allergic reactions within speciﬁc immunity in vivo. According to the results, it is established that experimental products have no negative eﬀect on the clinical parameters of laboratory animals. During the experiment, with the introduction of experimental products into diet, the dynamics of body weight changes in all groups of animals was positive. At the end of the experiment, there were smaller increase in the weight of rats and lower values of weight gain (Group 1 — 14.0 %, Group 2 — 15.9 %, Group 3 — 20.2 %). This is possibly due to the adaptation processes occurring in response to introduction of meat systems into the diet, which conﬁrms the leveling of the daily weight gain of experimental and intact animals since the 16th day of the experiment. According to the results of clinical blood analysis of the animals consuming experimental products, an increase is detected in leukocytes and lymphocytes by up to 18 %; in granulocytes by up to 35 %; and in monocytes by up to 8 %; in hemoglobin concentration, hematocrit and mean corpuscular hemoglobin concentration by more than 3 %; in red cell distribution width and mean corpuscular volume by up to 2 %, in comparison with intact animals. The correlation of these data with ELISA parameters for serum of experimental animals (histamine and immunoglobulin E) allowed to suggest the expression of reaginic antibodies and interaction on the surface of basophils and mast cells, which led to the degranulation and release (increase) of histamine, as a vasoactive factor, by 40 % compared with intact animals.The overall conclusion of the studies is that experimental model meat systems may trigger the activation of speciﬁc immune responses in laboratory animals. This is possibly due to protease-mediated formation of greater amount of indigestible polypeptides and peptides that invoke local adaptation responses.